Application of artificial intelligence and machine learning in expert systems for the mining industry: modern methods and technologies - Mutovina, Natalya; Nurtay, Margulan; Kalinin, Alexey; Tomilov, Aleksandr; Tomilova, Nadezhda (International Journal of Electrical and Computer Engineering (IJECE), 2025)
The mining industry has changed significantly in recent decades with the introduction of advanced technologies such as artificial intelligence (AI) and machine learning (ML). These innovations contribute to the creation of expert systems that help in optimizing processes, increasing the safety and sustainability of operations. This article is a literature review of modern AI and ML methods and technologies used in the mining industry. Discusses various intelligent and expert systems used to improve productivity, reduce operating costs, improve occupational safety, environmental sustainability, machine automation, predictive analytics, quality monitoring and control, and inventory and logistics management. The advantages and disadvantages of different approaches are analyzed, as well as their potential impact on the future of the mining industry. The review highlights the importance of integrating AI and ML into mining processes to achieve more efficient and safer solutions.